Automatic DVB Performance Measurement Tool - Yang, Dan (My University, 2010)
Nowadays, there are several different standards that specify what performance should expect from a DVB (Digital Video Broadcasting) receiver, such as NorDig Unified, DTG D-Book and EICTA MBRAI. These standards are complicated and thousands of measurements are involved, so it would be very handy to repeat the measurements with an automatic tool. In this thesis work, only NorDig Unified 2.1 is concerned. Since the test cases in NorDig Unified requirements for integrated receiver decoders are quite similar and repeatable, the work efficiency to fully evaluate the DVB performance could be improved by an automatic application. It would increase the test quality and decrease the manual labor a lot for each product. Implementation of the tool is the most important part in this project. The application runs on a computer with a user friendly graphical interface. Its main task is to control the calibrated signal generator (Rohde & Schwarz SFU) and test the set-top boxes (STB) in Motorola product range. Besides, a database has been designed to store all these testing results, and analysis on the data has been presented as well. In this project, the automatic DVB performance measurement tool is developed in Microsoft Visual C++ 6.0 with an ODBC (Open Database Connectivity) driver connecting to the database, and data presentation is done in Microsoft Excel 2003 using VBA (Visual Basic for Application).
Keywords: Datavetenskap (datalogi); Computer Science